Integrated EFL Teaching Practice: A Case Study in Speaking Class - Paramita Dharmayanti, Putu Ayu; Ari Wiryadi Joni, Dewa Ayu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2025)
This study aimed to evaluate integrated English as a Foreign Language (EFL) teaching practice in a speaking class. Three areas of integration were examined: technology integration, integration of 21st-century skills (4Cs), and language skills integration. Employing a case study method, this research focused on one lecturer purposively selected for actively implementing integrated instructional practices. Data were collected through classroom observations conducted during two online meetings via Zoom. The findings indicate that the lecturer successfully integrated technology through the use of Zoom, Google Classroom, YouTube, and WhatsApp, which supported student engagement, enhanced understanding, and extended learning opportunities based on the Triple E framework. Additionally, the 4Cs—critical thinking, creativity, communication, and collaboration—were incorporated through discussion activities, information searching, evaluation tasks, and a group video presentation project. The lecturer also integrated all four language skills (listening, speaking, reading, and writing), despite the primary focus on speaking. Overall, the integrative teaching practices were found to optimize students’ learning experiences and strengthen the effectiveness of EFL instruction.